Spatiotemporal Patterns of Loco-Regional Recurrence After Breast-Conserving Surgery - Qu, Fei-Lin; Mao, Rui; Liu, Zhe-Bin; Lin, Cai-Jin; Cao, A-Yong; Wu, Jiong; Liu, Guang-Yu; Yu, Ke-Da; Di, Gen-Hong; Li, Jun-Jie; Shao, Zhi-Ming (Frontiers in Oncology, 2021)
Background: Loco-regional recurrences (LRR) following breast-conserving surgery (BCS) remain a heterogeneous class of disease that has significant variation in its biological behavior and prognosis. Methods: To delineate the spatiotemporal patterns of LRR after BCS, we analyzed the data of 4325 patients treated with BCS from 2006 to 2016. Clinico-pathological and treatment specific factors were analyzed using the Cox proportional hazards model to identify factors predictive for LRR events. Recurrence patterns were scrutinized based on recurrence type and recurrence-free interval (RFI). Annual recurrence rates (ARR) were compared according to recurrence type and molecular subtype. Results: With a median follow-up of 66 months, 120 (2.8%) LRRs were recorded as the first site of failure. Age, pathologic stage, and molecular subtype were identified as predictors of LRR. The major recurrence type was ipsilateral breast tumour recurrence, which mainly (83.6%) occurred ≤5y post surgery. In the overall population, ARR curves showed that relapse peaked in the first 2.5 years. Patients with regional nodal recurrence, shorter RFI, and synchronous distant metastasis were associated with a poorer prognosis. HER2-positive disease had a higher rate of LRR events, more likely to have in-breast recurrence, and had an earlier relapse peak in the first 2 years after surgery. Conclusions: LRR risk following BCS is generally low in Chinese ethnicity. Different recurrence patterns after BCS were related to distinct clinical outcomes. Management of LRR should be largely individualized and tailored to the extent of disease, the molecular profile of the recurrence, and to baseline clinical variables.